e/ 153 – { 120 : [ 8 – ( 21 + 36 : 32 ) + 2012 0 ] }
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
153 - { 120 : [ 82 - ( 21 + 36 : 32 ) + 20120 ]}
= 153 - { 120 : [ 64 - ( 21 + 36 : 9 ) + 1 ]}
= 153 - { 120 : [ 64 - 25 + 1 ]}
= 153 - { 120 : [ 64 - 25 + 1 ]}
= 153 - { 120 : 40 }
= 153 - 3
= 150.
#Jiin
![](https://rs.olm.vn/images/avt/0.png?1311)
a) 5x = 120 : 2
5x = 60
x = 60 : 5
x = 12
b) 3x + 27 = 45
3x = 45 - 27
3x = 18
x = 18 : 3
x = 6
c) 73 + x - 122 = 234 : 2
73 + x - 122 = 117
73 + x = 117 + 122
73 + x = 239
x = 239 - 73
x = 166
d) 32 - 2(x - 1) = 12
2(x - 1) = 32 - 12
2(x - 1) = 20
x - 1 = 20 : 2
x - 1 = 10
x = 10 + 1
x = 11
e) 3(x + 1) - 15 = 36
3(x + 1) = 36 + 15
3(x + 1) = 51
x + 1 = 51 : 3
x + 1 = 17
x = 17 - 1
x = 16
f) 21 - (4x - 16) = 21
4x - 16 = 21 - 21
4x - 16 = 0
4x = 0 + 16
4x = 16
x = 16 : 4
x = 4
g) 13x - 3x = 500
10x = 500
x = 500 : 10
x = 50
h) 9x + x - 35 = 65
10x - 35 = 65
10x = 65 + 35
10x = 100
x = 100 : 10
x = 10
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(6x-36=5^{12}:5^{10}-2012^0\)
\(6x-36=5^2-2012^0\)
\(6x-36=25-1\)
\(6x-36=24\)
\(6x\) \(=24+36\)
\(6x\) \(=60\)
\(x=60:6\)
\(x=10\)
Vậy \(x=10\)
b) \(2x-125=-65\)
\(2x\) \(=\left(-65\right)+125\)
\(2x\) \(=60\)
\(x=60:2\)
\(x=30\)
Vậy \(x=30\)
c) \(2012-120\left(4x+1\right)=932\)
\(120\left(4x+1\right)=2012-932\)
\(120\left(4x+1\right)=1080\)
\(4x+1=1080:120\)
\(4x+1=9\)
\(4x\) \(=9-1\)
\(4x\) \(=8\)
\(x=8:4\)
\(x=2\)
Vậy \(x=2\)
a) 6x - 36 = 512 : 510 - 20120
6x - 36 = 52 - 20120
6x - 36 = 25 - 1
6x - 36 = 24
6x = 24 + 36
6x = 60
x = 60 : 6
x = 10
Vậy x = 10
b) 2x - 125 = -65
2x = (-65) + 125
2x = 60
x = 60 : 2
x = 30
Vậy x = 30
c) 2012 - 120(4x + 1) = 932
120(4x + 1) = 2012 - 932
120(4x + 1) = 1080
4x + 1 = 1080 : 120
4x + 1 = 9
4x = 9 - 1
4x = 8
x = 8 : 4
x = 2
Vậy x = 2.
Chúc bạn học tốt!
![](https://rs.olm.vn/images/avt/0.png?1311)
1) 5x = 120 : 2
5x = 60
x = 60 : 5
x = 12.
2) 3x + 27 = 45
3x = 45 - 27
3x = 18
x = 18 : 3
x = 6.
3) 73 + x - 122 = 234 : 2
73 + x - 122 = 117
73 + x = 117 + 122
73 + x = 239
x = 239 - 73
x = 166.
4) 32 - 2 ( x - 1 ) = 12
2 ( x - 1 ) = 32 - 12
2 ( x - 1 ) = 20
x - 1 = 20 : 2
x - 1 = 10
x = 10 + 1
x = 11.
5) 3 ( x + 1 ) - 15 = 36
3 ( x + 1 ) = 36 + 15
3 ( x + 1 ) = 51
x + 1 = 51 : 3
x + 1 = 17
x = 17 - 1
x = 16.
6) 32 - ( 4x - 16 ) = 21
4x - 16 = 32 - 21
4x - 16 = 11
4x = 11 + 16
4x = 27
x = 27 : 4
x = 6,75.
7) 13x - 3x = 500
( 13 - 3 )x = 500
10x = 500
x = 500 : 10
x = 50.
8) 9x + x - 35 = 68
9x + 1x - 35 = 68
9x + 1x = 68 + 35
9x + 1x = 103
( 9 + 1 )x = 103
10x = 103
x = 103 : 10
x = 10,3.
1) 5x = 120 : 2
5x = 60
x = 60 : 5
x = 12.
2) 3x + 27 = 45
3x = 45 - 27
3x = 18
x = 18 : 3
x = 6.
3) 73 + x - 122 = 234 : 2
73 + x - 122 = 117
73 + x = 117 + 122
73 + x = 239
x = 239 - 73
x = 166.
4) 32 - 2 ( x - 1 ) = 12
2 ( x - 1 ) = 32 - 12
2 ( x - 1 ) = 20
x - 1 = 20 : 2
x - 1 = 10
x = 10 + 1
x = 11.
5) 3 ( x + 1 ) - 15 = 36
3 ( x + 1 ) = 36 + 15
3 ( x + 1 ) = 51
x + 1 = 51 : 3
x + 1 = 17
x = 17 - 1
x = 16.
6) 32 - ( 4x - 16 ) = 21
4x - 16 = 32 - 21
4x - 16 = 11
4x = 11 + 16
4x = 27
x = 27 : 4
x = 6,75.
7) 13x - 3x = 500
( 13 - 3 )x = 500
10x = 500
x = 500 : 10
x = 50.
8) 9x + x - 35 = 68
9x + 1x - 35 = 68
9x + 1x = 68 + 35
9x + 1x = 103
( 9 + 1 )x = 103
10x = 103
x = 103 : 10
x = 10,3.
![](https://rs.olm.vn/images/avt/0.png?1311)
a, \(\sqrt{2x-1}=\sqrt{5}\)bình phương 2 vế ta được :
\(2x-1=5\Leftrightarrow x=3\)
b, \(\sqrt{x-5}=3\)bình phương 2 vế ta được :
\(x-5=9\Leftrightarrow x=14\)